化简 1、cosθ*tanθ 2、 (1-sinθ)(1+sinθ)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 18:35:27
化简1、cosθ*tanθ2、(1-sinθ)(1+sinθ)化简1、cosθ*tanθ2、(1-sinθ)(1+sinθ)化简1、cosθ*tanθ2、(1-sinθ)(1+sinθ)cosθ*ta
化简 1、cosθ*tanθ 2、 (1-sinθ)(1+sinθ)
化简 1、cosθ*tanθ 2、 (1-sinθ)(1+sinθ)
化简 1、cosθ*tanθ 2、 (1-sinθ)(1+sinθ)
cosθ*tanθ =sinθ
(1-sinθ)(1+sinθ)
=1-(sinθ)^2
=(cosθ)^2
sinθ,cos2θ
1,你知道tan=sin/cos.吗。。。。
不就是结果就是。。。sin
2,乘一下,结果是1-sin²θ=cos²θ
利用的公式就是s²+c²=1
(1-tan^4θ)cos^2θ+tan^2θ
三角比 1/tanθ-cos^2θ/tanθ
化简[(tanθ*sinθ)/(tanθ-1)] +[ cosθ/(1-tanθ) ]
化简:1.cosθtanθ 2.2cosα²-1/1-2sin²α
化简(sinθ-cosθ)/(tanθ-1)
化简 1/cos²θ√(1+tan²θ)
化简tanθ-1分之sinθ-cos等于
化简:cosθtanθ
化简(sinθ-cosθ)/(tanθ-1)A.tanθ B.sinθ C.-sinθ D.cosθ
求证2(cosθ -sinθ )/1+sinθ +cosθ =tan(π/4-θ /2)-tanθ /2
求证:2(cos θ -sin θ )/(1+sinθ +cosθ)=tan(∏/4- θ /2)-tan(θ /2)
cos θ/(1-tan θ)怎样化成cos θ/[(cosθ-sinθ)/cosθ]
tanθ+cosθ=1那么(tanθ)^2+(cotθ)^2=?急
(1-tanθ^4)*cosθ^2+tanθ^2如何化简,
已知cos[α+θ)=1求证:tan(2α+θ)+tanθ=0
已知cos[α+θ)=1求证:tan(2α+θ)+tanθ=0
证明1-2cos^2θ/tanθ-cotθ=sinθcosθ
已知tan(θ+π/4)=-2,求cosθ平方+sinθcosθ-1